The Genus Cladosporium: A Rich Source of Diverse and Bioactive Natural Compounds - Maria Michela Salvatore; Anna Andolfi; Rosario Nicoletti (Molecules, 2021)
Fungi are renowned as one of the most fruitful sources of chemodiversity and for their ubiquitous occurrence. Among the many taxonomic groupings considered for the implications deriving from their biosynthetic aptitudes, the genus Cladosporium stands out as one of the most common in indoor environments. A better understanding of the impact of these fungi on human health and activities is clearly based on the improvement of our knowledge of the structural aspects and biological properties of their secondary metabolites, which are reviewed in the present paper.